Effectiveness of hyperbaric oxygen for experimental treatment of schistosomiasis mansoni using praziquantel-free and encapsulated into liposomes: Assay in adult worms and oviposition - Frezza, Tarsila Ferraz; Souza, Ana Luiza Ribeiro de [UNESP]; Prado, César Corat Ribeiro; Oliveira, Claudineide Nascimento Fernandes de; Gremião, Maria Palmira Daflon [UNESP]; Giorgio, Selma; Dolder, Mary Anne Heidi; Joazeiro, Paulo Pinto; Allegretti, Silmara Marques (Elsevier B. V., 2015)
The treatment of schistosomiasis depends on a single drug: praziquantel (PZQ). However, this treatment presents limitations such as low and/or erratic bioavailability that can contribute to cases of tolerance. Improvements to the available drug are urgently needed and studies with a controlled system of drug release, like liposomes, have been gaining prominence. The present study evaluated the activity and synergy between liposomal-praziquantel (lip.PZQ) and hyperbaric oxygen therapy (HBO). Mice received doses of 60 or 100mg/kg PZQ or lip.PZQ, 50 days post-infection, and after the treatment, were exposed to HBO (3 atmosphere absolute - ATA) for 1h. The viability of adult worms and oviposition were analyzed, by necropsy and Kato-Katz examination performed after 15 days of treatment. A concentration of 100mg/kg of lip.PZQ+HBO was more effective (48.0% reduction of worms, 83.3% reduction of eggs/gram of feces) and 100% of the mice had altered of oograms (indicating interruption of oviposition) compared to other treatments and to the Control group (infected and untreated). It is known that PZQ requires participation of the host immune system to complete its antischistosomal activity and that HBO is able to stimulate the immune system. The drug became more available in the body when incorporated into liposomes and, used with HBO, the HBO worked as an adjuvant. This explains the decreases of oviposition and worms recovered form hepatic portal system.
Keywords: Hiperbaric-oxigen; In vivo assay; Liposomal-praziquantel; Praziquantel; Schistosoma mansoni